(3GdefgL GdJfehj GdHOjd aj GdEbJUGO GdESdGej (B:s (3OQGSI ddeaGgje hGdCgOGa hGdChdhjGJ hJMdjd ddCQcGf hGdSjGSGJ hGdeDSSGJ (B/s - (3UGdMj, UGdMs ((3GdbGgQI(B: s (3OGQ GdaLQ(B, s, 2006)
(3WHjYI GdYedjI hCgOGagG hChdhjGJgG aj GdefgL GdJfehj GdHOjd QDjI fXQjI LOjOI deQGLYI GdeaGgje hGdfXQjGJ hJMOjO GdCgOGa hGdChdhjGJ(B-(3CQcGf hSjGSGJ heDSSGJ GdefgL GdJfehj GdHOjd(B-(3OQGSI dNUhUjI GdefgLs
Keywords: (3GdEbJUGO GdESdGejs; (3GdefgL GdJfehjs